A Challenge in Governance: A Case of Higher Education in Pakistan. Issue 2 (September 2019) - Butt, Arif Nazir; Hemani, Shezeen Salim
This case documents the governance challenges faced by Namal's Board of Governors. Namal College (Namal) was the brainchild and dream project of Imran Khan—world-renowned cricketer, philanthropist and one of the most popular politicians of Pakistan. This case narrates the journey of Namal College from its inception in 2002 until August 2014. At this juncture, Abdul Razak Dawood (ARD), the Vice Chairman of Namal's Board, contemplated the challenges that Namal faced and the role the Board and its members could play in taking the college closer to its vision. From its humble beginnings as a technical training and diploma-awarding institute, Namal managed to achieve several milestones in one decade of its existence. One of the most notable achievement was the acquisition of a 1, 000-acre land. ARD, a graduate from Columbia University, a leading industrialist and the founder of one of Pakistan's largest engineering company, Descon Engineering, wondered what would it take to create a high-powered and effective Board? ARD was concerned about addressing Namal's challenges, which included governance, management, funding, academics and construction issues. The question was what role could the Board play in doing so? More explicitly, what role could each Board member play? Was there a possibility of creating committees within the Board to ensure efficient functioning and accountability? In sum, the case revolves around critical governance issues that needed to be addressed to ensure Namal's sustainability and growth.